Wind Energy Systems for Electric Power Generation - Stiebler, Manfred. (Green Energy and Technology,, 2008)
This book deals with Wind-Energy systems and their implementation into the grid, with focus on electrical engineering. Starting from a view on wind as a prominent source of renewable energy, it describes properties and performance of wind turbines, electrical generators and power electronic converters which are the main components of wind energy systems. Much attention is spent on system control, grid implementation and aspects of power quality. In this way, the book provides fundamental knowledge for graduate students, designers and practicing engineers.